The putative mevalonate diphosphate decarboxylase from Picrophilus torridus is in reality a mevalonate-3-kinase with high potential for bioproduction of isobutene - Rossoni, Luca; Hall, Stephen J.; Eastham, Graham; Licence, Peter; Stephens, Gill (American Society for Microbiology., 2015)
Mevalonate diphosphate decarboxylase (MVD) is an ATP-dependent enzyme that catalyzes the phosphorylation/decarboxylation of (R)-mevalonate-5-diphosphate to isopentenyl pyrophosphate in the mevalonate (MVA) pathway.MVD is a key enzyme in engineered metabolic pathways for bioproduction of isobutene, since it catalyzes the conversion of 3-hydroxyisovalerate (3-HIV) to isobutene, an important platform chemical. The putative homologue from Picrophilus torridus has been identified as a highly efficient variant in a number of patents, but its detailed characterization has not been reported. In this study, we have successfully purified and characterized the putative MVD from P. torridus. We discovered that it is not a decarboxylase per se but an ATP-dependent enzyme, mevalonate-3-kinase (M3K), which catalyzes the phosphorylation of MVA to mevalonate-3-phosphate. The enzyme’s potential in isobutene formation is due to the conversion of 3-HIV to an unstable 3-phosphate intermediate that undergoes consequent spontaneous decarboxylation to form isobutene. Isobutene production rates were as high as 507 pmol min-1 g cells-1 using Escherichia coli cells expressing the enzyme and 2,880 pmol min-1 mg protein-1 with the purified histidine-tagged enzyme, significantly higher than reported previously. M3K is a key enzyme of the novel MVA pathway discovered very recently in Thermoplasma acidophilum. We suggest that P. torridus metabolizes MVA by the same pathway.